Análise da gestão da propriedade intelectual e da transferência da tecnologia nas universidades do Rio de Janeiro - Pereira, Valdecy (2008)
The innovation firm in the international scene as a need that concerns not only the survival of companies but also the survival of nations. The globalized world and current technologies have enabled a breakthrough in speed propagation and dissemination of knowledge and thus the increasingly evidences in systems to protect intellectual property in several countries, that knowledge must be protected and encouraged to grow because of its stimulus and its growth is that dictate the future prosperity. With that concern in the background, the study aims to investigate through a case study, the Centers for Technological Innovation of four universities in the state of Rio de Janeiro. Noting its adequacy and raising the main problems arising from the requirements imposed by the Law of Innovation